Efficacy of Trial Fitting and Software Fitting for Orthokeratology Lens: One-Year Follow-Up Study. Issue 5 (September 2018) - Lu, Daqian; Gu, Tianpu; Lin, Weiping; Li, Na; Gong, Boteng; Wei, Ruihua
Abstract : Objective: To observe and compare the clinical efficacy of 1-year trial fitting and software fitting orthokeratology lenses. Methods: One hundred myopes who received vision correction with the use of orthokeratology lenses form July 2016 to September 2017 were included in this study. Subjects were assigned randomly into the two groups: the trial fitting group (group A) and the software fitting group (group B). For the right eye of each subject, measurements, such as uncorrected visual acuity (UCVA, logarithm of minimal angle of resolution), refractive error, corneal topography, ocular health status, and the fitting situation, were obtained at baseline, 1 week, 1 month, 3 months, 6 months, and 12 months after lens wear. Axial length and corneal endothelium cells (CECs) were also measured at baseline and 12 months after wearing the lens. Results: Compared with the baseline, the spherical equivalent refraction, UCVA, and central corneal curvature changed significantly after orthokeratology (OK) lens wear (all P <0.05). Between groups A and B, the parameters aforementioned were insignificant at each time point (all P >0.05). Axial length and CECs showed no significant changes during the first year of OK treatment (all P >0.05). Rate of corneal staining between two groups revealed no difference during 1-year visit ( P <0.05). Conclusion: Both the trial lens fitting and software fitting approaches were effective in temporarily reducing myopia, providing good UCVA and delaying the elongation of axial length for moderate and high myopic adolescents. Both the two approaches can be combined in OK lens fitting.